Religious Education for Non-Muslim Students in Aceh: An Evaluation of Inclusivity and Implementation - Suharman Suharman; Tengku Hafinda; Nur Rohman; Rahmad Syah Putra; Khairuddin Hasan; Maya Agustina; Farah Sumaiyah (AL-ISHLAH: Jurnal Pendidikan, 2025)
The right to religious education for all students is guaranteed by Indonesian law. However, in Muslim-majority regions such as Aceh, the implementation of religious education for non-Muslim students remains inconsistent and under-explored. This study investigates how such education is implemented and evaluated in public schools, with a focus on inclusivity and compliance with legal standards. Using a qualitative phenomenological approach, the study explored the lived experiences of principals, religious teachers, non-Muslim students, and religious leaders across four regions in Aceh: Aceh Singkil, West Aceh, Sabang, and Lhokseumawe. Data were collected through semi-structured interviews, questionnaires, and document analysis, and analyzed using thematic triangulation. Findings reveal that due to the lack of non-Muslim religious teachers, schools rely on external religious leaders to provide instruction and conduct evaluations. Most learning takes place in houses of worship and is integrated into regular religious activities. While schools facilitate this process, the absence of standardized curricula and assessment rubrics has led to inconsistent learning outcomes and unequal educational experiences for minority students. The study identifies a hybrid model of religious education delivery that partially fulfills legal obligations but lacks integration with national educational standards. It concludes that while efforts to provide religious education for non-Muslim students exist, they are fragmented and depend heavily on local initiatives. A national policy framework is urgently needed to ensure equitable, inclusive, and accountable religious education for all students.